Wet chemical synthesis and electrochemical performance of novel double perovskite Y2CuMnO6 nanocrystallites. (1st March 2020) - Mansoorie, Farha Naaz; Singh, Jashandeep; Kumar, Ashok
Abstract: We report facile chemical synthesis of novel double perovskite Y2 CuMnO6 nanocrystallites by a wet chemical sol gel process. The formation of Y2 CuMnO6 has been confirmed by X-ray diffraction, Raman spectrum analysis and X-ray photoelectron spectroscopy. The Y2 CuMnO6 exhibited monoclinic structure with P21 /n symmetry; lattice parameters being a = 5.2977 Å, b = 5.7561 Å, c = 7.5823 Å, and β = 89.8766°. The Raman spectrum revealed modes at 649 cm −1, 436 cm −1, 350 cm −1, 326 cm −1 for symmetry Ag, and at 616.04 cm −1 and 513.5 cm −1 for symmetry Bg corresponding to monoclinic P21 /n space group. The X-ray photoelectron spectra exhibited presence of Y 3+, Cu 2+ and Mn 4+ species at the surface of the Y2 CuMnO6 . The specific capacitance 15.6 F g −1, energy density 0.43 W h/kg, and power density 56.2 W/kg were obtained at the current density of 0.2 A/g. Further, Y2 CuMnO6 nano-crystallites electrode has shown the specific capacitance retentivity of 75% for 1000 cycles.